2016
DOI: 10.1016/j.jalz.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the human hippocampal proteome at all pathologic stages of Alzheimer's disease

Abstract: This study provides new insight into AD-dependent changes in protein levels in the hippocampus during AD pathology, identifying potential novel therapeutic targets and biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 54 publications
11
142
0
Order By: Relevance
“…Notably, Aß affects synapse loss in AD hippocampus by disruption of Ncam2 [22] and overexpression of wild-type PS1 or PS1 with a familial AD mutation (M146L) leads to decreased sialylation of Ncam in the neuroblastoma cell line SH-SY5Y [23]. Recently, Hondius et al demonstrated that the human post-mortem AD hippocampus has an altered expression of a number of proteins associated with extracellular matrix components and calcium-dependent signalling proteins that are linked to early changes in cytoskeletal dynamics and synaptic plasticity over the different Braak stages compared to matched controls [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, Aß affects synapse loss in AD hippocampus by disruption of Ncam2 [22] and overexpression of wild-type PS1 or PS1 with a familial AD mutation (M146L) leads to decreased sialylation of Ncam in the neuroblastoma cell line SH-SY5Y [23]. Recently, Hondius et al demonstrated that the human post-mortem AD hippocampus has an altered expression of a number of proteins associated with extracellular matrix components and calcium-dependent signalling proteins that are linked to early changes in cytoskeletal dynamics and synaptic plasticity over the different Braak stages compared to matched controls [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Among 372 altered proteins, several ECM components were increased in AD, including tenascin, versican, laminin subunit beta-2, and galectin-1. In addition, increases in adhesion molecules that interact with ECM, including CD44, integrin β1, and integrin αV were observed in AD [134]. In contrast, versican and tenascin-R were significantly decreased in frontal cortex AD brain tissue [135].…”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%
“…Intriguingly, versican, one of the hyalectans, was differentially expressed in three out of six studies [78, 134, 135], reporting differential expression of ECM proteins. Notably, all three studies were performed as shotgun proteomics experiments, with label-free LC-MS/MS analysis, using an LTQ-Orbitrap instrument.…”
Section: Current State Of Proteomics In Studies Of Neurodegenerative mentioning
confidence: 99%
See 2 more Smart Citations